Pseudomyxoma Peritonei - A Case Report - Tuladhar, Ruhee; Shrestha, Eliza; Shrestha , Rishikesh Narayan; Thapa, Anita; Rajak, Ashik (Journal of Nepal Health Research Council, 2021)
A 53-year-old lady presented with post-menopausal bleeding (spotting) for two days and abdominal pain for three months. CT scan revealed bilateral adnexal mass and ascites; and CEA and CA19.9 was raised. Histopathology of the resected tissues revealed mucinous carcinoma of bilateral ovaries and colon with omental metastasis. Generally, pseudomyxoma peritonei arises from primary ovarian or appendiceal adenomas or adenocarcinomas. Keywords: Adenocarcinomas; ascites; metastases; mucinous carcinoma; pseudomyxoma peritonei